(untitled) (Stavební obzor - Civil Engineering Journal, 2015)
Durability of the structures is one of the most discussed issues of last decades. It is one of the most easily measured properties for analysis during the structural lifetime. Concrete deflections increase over time due to rheological effects (creep and shrinkage) in addition cyclic creep can be observed on the cyclically loaded structures. The deflection increase due to the cyclic creep is not properly quantified. The fatigue damage function presented in this paper provides an analytical solution for the deflection development due to cyclic loading. The evaluation of the deflection is based on the reduction of the initial modulus of elasticity. Main principles of the function are discussed and compared with the standardized approaches for the fatigue assessment. Experimental verification of the fatigue damage function was carried out on reinforced concrete specimens and on prestressed concrete slab. To improve the standardized approaches, the real stress distribution was considered with the use of newly-developed method of partial integration over the height of the specimen compressive zone. The deflection increase due to cyclic loading was measured regularly with inductive displacement transducer. Comparison of the measured values and the values calculated using the presented function shows good agreement. The fatigue damage function can be used easily in “in-hand” calculations, or can be inserted into FEM-based software and used in practical applications for assessing the increase in the deformations of concrete structural elements caused by cyclic loading.